A three-dimensional numerical approach on water entry of a horizontal circular cylinder using the volume of fluid technique. (15th January 2017) - Iranmanesh, A.; Passandideh-Fard, M.
Abstract: In this paper, complicated hydrodynamics of a horizontal circular cylinder entering water is investigated numerically for low Froude numbers. A numerical approach is used to model the solid-liquid interactions in presence of a free-surface. The governing equations for the 3D incompressible fluid flow are continuity and Navier-Stokes equations along with an equation for the free surface advection. To track the free-surface motion, the fast-fictitious-domain method is integrated into the volume-of-fluid (VOF) technique. The governing equations are solved everywhere in the computational domain including the horizontal cylinder. A rigid body motion is applied to the region occupied by the circular cylinder. The no-slip boundary condition on the solid-liquid interface is exerted implicitly via increasing the viscosity of the region occupied by the solid. To validate the numerical scheme, the results are compared with those of the experiments available in the literature. The effects of cylinder diameter, length, impact velocity, and cylinder-water density ratio on the non-dimensional depth are also investigated. Highlights: A 3D numerical approach is presented to simulate the solid-liquid interaction. The free surface interface is tracked using the VOF method. The no slip boundary condition is exerted by increasing the viscosity. The effect of diameter on the cylinder motion is studied numerically.